The Civic Ascension of Unanue - Paz-Soldán, Carlos Enrique (1955)
We work in the morning, teachers and students of the house where doctrine in Peru to embrace the profession to alleviate the pain, cost of living; to attend to ailments, few heritage born; and to ensure the health of the people, the supreme civic duty to perform, together with representatives of public power and with this select audience representative of the public, offering renewed allegiance to the pure sacred memory of the Founder who laid the foundations of the Medical School of Lima.